2018
DOI: 10.1093/jas/sky335
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of energy supplementation on growth performance and immune response of suckling pigs

Abstract: Three studies were performed to determine the effects of oral energy sources on the performance, immune status, and intestinal morphology of piglets. In Exp. 1, 50 litters were selected based on genotype and parity order to determine the optimum amount of supplemental energy for neonatal pigs. They were distributed according to a 5 × 5 Latin square design, in which columns were represented by 5 sows and rows were represented by 5 newborn weight categories. Treatments consisted of 2 oral doses of 0, 2, 4, 8, or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 26 publications
0
8
0
2
Order By: Relevance
“…A later study, in which LBW piglets were supplemented with coconut oil on the day of birth and the second day, also did not show a reduced mortality when comparing supplemented and non-supplemented piglets. It must be mentioned, though, that during the latter study, piglets with a higher birth weight (<1.20 kg) were classified as LBW and the total supplemented energy was lower than the previously mentioned studies [ 41 ]. The results of these last two studies support the hypothesis that drenching could nullify a potentially positive effect of the supplemented product.…”
Section: Discussionmentioning
confidence: 76%
“…A later study, in which LBW piglets were supplemented with coconut oil on the day of birth and the second day, also did not show a reduced mortality when comparing supplemented and non-supplemented piglets. It must be mentioned, though, that during the latter study, piglets with a higher birth weight (<1.20 kg) were classified as LBW and the total supplemented energy was lower than the previously mentioned studies [ 41 ]. The results of these last two studies support the hypothesis that drenching could nullify a potentially positive effect of the supplemented product.…”
Section: Discussionmentioning
confidence: 76%
“…However, other parameters related to lipid metabolism, such as triglycerides and cholesterol, which were not analyzed in this study, are more frequently affected by glycerin addition [ 10 , 23 , 39 , 41 , 42 ]. In this sense, Narayan and Mcmullen [ 43 ] showed that glycerin metabolism in the livers of mice and birds after chronic intake has a stimulatory effect on the synthesis of free fatty acids, triglycerides, cholesterol, chylomicrons, and plasmatic lipoproteins.…”
Section: Discussionmentioning
confidence: 99%
“…Means with different letters within a line are significantly different (P<0.05) weight gain was obtained when feeding the lactating sows with coconut oil rather than fish oil (Lauridsen and Danielsen, 2004). Furthermore, oral supplementation of coconut oil to low-weight piglets tended to increase body weight during the first week (Manzke et al, 2018), and in another experiment of this study oral supplementation of rice-bran oil to pigs increased the weaning weight (Manzke et al, 2018). Unpublished data (C.L., personal communication) showed that feeding sows with lipid sources at a level of 8% of octanoic acid (4%) in combination with fish oil (4%) increased the sow milk concentration of C8:0, which was present with 0.12%, whereas when other dietary treatments (8% of either coconut oil, fish oil, or sunflower oil) were provided, the relative proportion of C8:0 was 0.04%.…”
Section: Transfer Of Fa To Pigletsmentioning
confidence: 92%
“…Inflammation often results in the repartitioning of the host's energy to functions other than digestion. An immediate energy supply in the form of various oils supplemented to newborn piglets had no influence on gut morphology (Manzke et al, 2018). The impact may be more pronounced in post-weaning pigs, as MCFA can be directly utilized by the enterocytes for energy production and thereby maintain the integrity of the intestinal tissue (Guillot et al, 1993).…”
Section: Intestinal Epithelium Functionmentioning
confidence: 97%